2021
DOI: 10.3389/fphys.2021.657452
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Left Atrial Fibrosis May Contribute to Aberrant Hemodynamics and Increased Risk of Stroke in Atrial Fibrillation Patients

Abstract: Atrial fibrillation (AF) patients are at high risk of stroke, with the left atrial appendage (LAA) found to be the most common site of clot formation. Presence of left atrial (LA) fibrosis has also been associated with higher stroke risk. However, the mechanisms for increased stroke risk in patients with atrial fibrotic remodeling are poorly understood. We sought to explore these mechanisms using fluid dynamic analysis and to test the hypothesis that the presence of LA fibrosis leads to aberrant hemodynamics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Compared with the non-LVZ group, the LAA-FV in the LVZ group was lower. This is consistent with the results of previous studies that show that there may be a correlation between atrial fibrosis and left atrial appendage velocity 13 , 14 . At present, TEE is the most widely used method to measure the function of the LAA, and it is considered the gold standard, but it is semi-invasive.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared with the non-LVZ group, the LAA-FV in the LVZ group was lower. This is consistent with the results of previous studies that show that there may be a correlation between atrial fibrosis and left atrial appendage velocity 13 , 14 . At present, TEE is the most widely used method to measure the function of the LAA, and it is considered the gold standard, but it is semi-invasive.…”
Section: Discussionsupporting
confidence: 93%
“…Epicardial adipose tissue (EAT) is in direct contact with the surface of the atrium and pulmonary vein and, like the myocardium, is supplied by the coronary artery 10 , which can play an important role in the occurrence and development of atrial fibrillation and stroke through a variety of mechanisms, such as fat infiltration, fibrosis and inflammation 11 , 12 . Previous studies have shown that myocardial fibrosis is closely related to the velocity of the left atrial appendage 13 , 14 . However, the relationship between epicardial adipose tissue and left atrial appendage velocity is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…A recent research reports that LA wall fibrosis detected by delayed magnetic resonance imaging is inversely proportional to LA strain and strain rate and is associated with AF. [27] . Thus, structural and functional remodeling of LA in patients with AF may be the result of atrial pathology itself, independent of left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is an irregular rhythm of the heart which is mainly characterized by arrhythmia, pulse disorder, palpitation, dizziness, chest discomfort, and shortness of breath [ 1 ]. Further, the main histological feature for AF is atrial fibrosis which is often caused by deposition of excessive fibrinogen due to dysregulation of extracellular matrix metabolism [ 1 , 2 ]. Several previous studies have shown that apoptosis of atrial myocytes and atrial fibrosis lead to deceleration of atrial conduction velocity which mediates the occurrence and development of AF [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%